2015
DOI: 10.1371/journal.pone.0135037
|View full text |Cite
|
Sign up to set email alerts
|

High Platelet Reactivity in Patients with Acute Coronary Syndromes Undergoing Percutaneous Coronary Intervention: Randomised Controlled Trial Comparing Prasugrel and Clopidogrel

Abstract: BackgroundPrasugrel is more effective than clopidogrel in reducing platelet aggregation in acute coronary syndromes. Data available on prasugrel reloading in clopidogrel treated patients with high residual platelet reactivity (HRPR) i.e. poor responders, is limited.ObjectivesTo determine the effects of prasugrel loading on platelet function in patients on clopidogrel and high platelet reactivity undergoing percutaneous coronary intervention for acute coronary syndrome (ACS).PatientsPatients with ACS on clopido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…However, the magnitude of the problem of HRPR on prasugrel treatment is still largely undefined, with its rate varying among studies according to the methods and definitions applied [13,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, the magnitude of the problem of HRPR on prasugrel treatment is still largely undefined, with its rate varying among studies according to the methods and definitions applied [13,36].…”
Section: Discussionmentioning
confidence: 99%
“…Double Loading Regimen of clopidogrel did not confer additional benefits on short-term and long-term outcomes in Asian patients with STEMI undergoing primary PCI: Clopidogrel has emerged as a mainstay in the management of patients with acute arterial occlusive syndrome over the past decade, as well as a principal component of PCI pharmacotherapy. [18][19][20][21][22][23] However, growing amounts of data have recently shown that poor response (i.e., drug resistance) to clopidogrel as measured by platelet reactivity units or with VerifyNow assay measured in P2Y12 reaction units (PRU) 31,32) occurs in some ACS patients in real-world clinical practice. [24][25][26] This situ-ation, resulting in high-risk thromboembolic events, undoubtedly causes poorer prognostic outcome in patients with ACS undergoing PCI.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] This situ-ation, resulting in high-risk thromboembolic events, undoubtedly causes poorer prognostic outcome in patients with ACS undergoing PCI. The results of these experimental and clinical studies [24][25][26]31,32) raise the question of whether a double dose regimen (i.e., 600 mg) of clopidogrel may improve clinical outcomes in ACS patients undergoing PCI. 33,34) However, other clinical trials 24,35) did not find the additional benefit of double regimen of clopidogrel as measured by angiographic findings and clinical outcome as compared to standard loading regimen (i.e., 300 mg) of clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area under the aggregation curve (AUC) was used as a measure of the overall platelet aggregation. Tests were performed within 30 min after taking blood (14).…”
Section: Multiplate Impedance Aggregometrymentioning
confidence: 99%